Монгол Орны Газрын Доорхи Усны Нөөцөд Усжсан Хагарлын Эзлэх Байр Суурь - Т, Улаанбаатар; M, Лэгдэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
The underground water resource can play important role in social, economic life in Mongolia suffering from extreme drought induced climate change. For instance, in order to predict of water resources in tectonic and shallow lithosphere rifts we are ecessary to invent new geophysical methods and instruments. Some results of a scientific and technological project, entitled “Assessment of surface and underground water resources in Mongolia using remote sensing, GIS and hydrogeophysical methods” supported by Ministry of Environment and Green Development of Mongolia are presented in this paper.